Structure, Effects and Deficiencies of an Entrepreneurial Ecosystem: the Spanish Case (Journal of Business, Universidad del Pacífico (Lima, Peru), 2017)
In this paper, we rely on the Spanish GEM Project to analyze the basic conditions that shape the profiles of the Spanish regional entrepreneurial ecosystem and to configure which aspects are given and which should be met in order for that ecosystem to be considered as a tool to support entrepreneurship and not just a wasteland. Although some media are incorporated, the nutrients needed for germination are not included.
Keywords: Entrepreneurship; Entrepreneurial Ecosystem; GEM